Introduction To The Themed Issue On Performance In Asia - Paul, Joshua (Penerbit Universiti Sains Malaysia (USM Press), 2014)
"Performance in Asia" is the second of two themed issues of the International Journal of Asia Pacific Studies (IJAPS). It follows part one, "Music in Asia," which appeared in IJAPS Volume 9, Issue 1. Like its counterpart, this themed issue brings together articles from various disciplines and regions across Asia, presenting research on Singapore, Taiwan, Pakistan and Japan. The material analysed ranges from live theatre, both avant-garde and popular, to puppet plays, film and television. The articles in this themed issue share a common focus on the experience of the spectator. The productions they analyse demonstrate how cross-cultural and other hybrid elements either make for a jarring spectatorial experience that leads to questions about locality and identity, or encourage audiences that have been hitherto defined by their differences to come together. Several of the articles in this themed issue also trace audiences across time, comparing their responses decades ago to those of today. In this fashion, the articles in "Performance in Asia" address the complex relationship between the global and the local in terms of how artistic productions impact upon both the individual, and the society in which that individual is located, in a rapidly changing world.